Peran Budaya Sekolah dalam Menciptakan Lingkungan Belajar yang Kondusif - Suwarni, Suwarni (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2022)
School culture plays a crucial role in creating a conducive learning environment for students. A conducive learning environment can help improve the quality of education and student learning outcomes. This study aims to explain how school culture can influence the formation of a conducive learning environment, as well as to explore the factors that affect the formation of such a school culture. The research method used in this study is a literature review by collecting data from relevant and reliable sources. The collected data is analyzed using qualitative analysis techniques (content analysis) to then be categorized and analyzed in identifying main patterns/themes. The results of data analysis are interpreted to find the relationship between school culture, the formation of a conducive learning environment, and the factors that affect the formation of such a school culture. The results of the study indicate that an inclusive, collaborative, and student-centered school culture can create a conducive learning environment. Factors such as leadership, communication, and student and parental participation also play important roles in shaping such a school culture.